Expression of Killer Immunoglobulin Receptor Genes among HIV-Infected Individuals with Non-AIDS Comorbidities - Farouk F. Abou Hassan; Mirna Bou Hamdan; Khalil El Asmar; Nada M. Melhem (Journal of Immunology Research)
Combined antiretroviral therapy (cART) increased the life expectancy of people living with HIV (PLHIV) and remarkably reduced the morbidity and mortality associated with HIV infection. However, non-AIDS associated comorbidities including diabetes, hypertension, hyperlipidemia, and cardiovascular diseases (CVD) are increasingly reported among PLHIV receiving cART. Killer cell immunoglobulin receptors (KIRs) expressed on the surface of natural killer (NK) cells have been previously implicated in controlling HIV disease progression. The aim of this study is to investigate the role of KIRs in developing non-AIDS associated comorbidities among PLHIV. Demographic and behavioral data were collected from voluntary participants using a standardized questionnaire. Whole blood samples were collected for KIR genotyping. Hypertension (29.5%) and hyperlipidemia (29.5%) followed by diabetes (23.7%) and CVD (9.7%) were mainly reported among our study participants with higher rate of comorbid conditions observed among participants>40 years old. The observed KIR frequency (OF) was ≥90% for inhibitory KIR2DL1 and KIR3DL1, activating KIR2DS4 and the pseudogene KIR2DP1 among study participants. We detected significant differences in the expression of KIR3DS4 and KIR3DL1 (p=0.038) between diabetic and nondiabetic and in the expression of KIR2DL3 between hypertensive and normotensive HIV-infected individuals (p=0.047). Moreover, KIR2DL1 and KIR2DP1 were associated with significantly reduced odds of having CVD (OR 0.08; 95% CI: 0.01-0.69; p=0.022). Our study suggests the potential role of KIR in predisposition to non-AIDS comorbidities among PLHIV and underscores the need for more studies to further elucidate the role of KIRs in this population.